Carbon supported Ag nanoparticles as high performance cathode catalyst for H2/O2 anion exchange membrane fuel cell - Xin, Le; Zhang, Zhiyong; Wang, Zhichao; Qi, Ji; Li, Wenzhen (Frontiers in Chemistry, 2013)
A solution phase-based nanocapsule method was successfully developed to synthesize non-precious metal catalyst - carbon supported Ag nanoparticles (Ag/C). XRD patterns and TEM image show Ag nanoparticles with a small average size (5.4 nm) and narrow size distribution (2-9 nm) are uniformly dispersed on the carbon black Vulcan XC-72 support. The intrinsic activity and pathway of oxygen reduction reaction (ORR) on the Ag/C and commercial Pt/C were investigated using rotating ring disc electrode (RRDE) tests at room temperature. The results confirmed that the 4-electron pathway of ORR proceeds on small Ag nanoparticles, and showed comparable ORR activities on the self-prepared Ag/C and a commercial Pt/C. A single H2-O2 anion exchange membrane fuel cell with the Ag/C cathode catalyst exhibited an open circuit potential of 0.98 V and a peak power density of 190 mW/cm2 at 80 oC.